2021
DOI: 10.3389/fped.2021.633525
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends and Future Prospects of Child Nutrition: A Bibliometric Analysis of Highly Cited Papers

Abstract: Child nutrition has always been a global concern. This study performed visual analysis of 1,398 child nutrition highly cited papers (HCPs) from 2009 to 2019. The purpose of the study was to evaluate and present the performances of authors, journals, countries, institutions, top cited papers; to explore the hot topics, prospects, and to propose the future research directions on child nutrition. We used bibliometric methods to conduct in-depth statistical analysis of HCPs on child nutrition, showing research pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
(88 reference statements)
0
9
0
1
Order By: Relevance
“…The United States, Italy, the United Kingdom, Germany, and Canada had the most binge eating research published in the literature, accounting for 83.8% of all publications in the study. Although no bibliometric study on BED has been published on BED, some studies have been conducted on nutrition research productivity in various fields[ 41 , 42 ], as measured by publications, and found that the United States, the United Kingdom, and Europe countries were the top producers of binge eating publications during this time. Eating disorders are more common in western societies than in non-western societies, although the incidence appears to be increasing[ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The United States, Italy, the United Kingdom, Germany, and Canada had the most binge eating research published in the literature, accounting for 83.8% of all publications in the study. Although no bibliometric study on BED has been published on BED, some studies have been conducted on nutrition research productivity in various fields[ 41 , 42 ], as measured by publications, and found that the United States, the United Kingdom, and Europe countries were the top producers of binge eating publications during this time. Eating disorders are more common in western societies than in non-western societies, although the incidence appears to be increasing[ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [22] used two tools in their study, CiteSpace, and VOSviewer, to perform bibliometric analysis. In this study, we used two bibliometric tools (Biblioshiny and bibliometric online application).…”
Section: Maın Informatıonmentioning
confidence: 99%
“…Although many reviews and meta-analyses can provide helpful data and reliable evidence-based medical conclusions, these techniques frequently fail to provide a comprehensive and integrated perspective for a particular field of research. Using bibliometric techniques, our research teams and other researchers have examined publication trends and research hotspots in the area of nutrition, including child nutrition [ 30 ], sports nutrition [ 31 ], nutrition and cancer [ 32 ], nutrition and dietetics [ 33 ], nutrition and COVID-19 [ 34 ], nutrition and microbiota [ 35 ], diets and breast cancer [ 36 ], dietary therapies for epilepsy [ 37 ], dietary factors of metabolic syndrome[ 38 ], Mediterranean diet [ 39 ], diet-related eHealth and mHealth [ 40 ], and HIV/AIDS and nutrition [ 41 ]. To the best of our knowledge, no prior bibliometric research has examined the most relevant scientific research on nutrition and depression.…”
Section: Introductionmentioning
confidence: 99%